Intertemporal Prices and the U.S. Trade Balance - Burda, Michael C.; Gerlach, Stefan (American Economic Review, 1992)
The deterioration of the U.S. merchandise trade deficit in the 1980s fell mostly on durable goods. Using a representative-agent model, the authors show that the key distinction between the trade balance in nondurables and durables is the role of intertemporal prices in the latter. A decrease in intertemporal prices associated, for example, with an exchange-rate overvaluation should, therefore, be expected to worsen the trade balance in durables more than in nondurables. This interpretation of the compositional changes of the U.S. trade balance is supported by their econometric findings. Copyright 1992 by American Economic Association.